Proposal for the definition of enterprise architecture (Dimensión Empresarial, 2020)
The Enterprise Architecture (AE) is one of the most important elements that is taking place within organizations, considering it a strategic mechanism that drives companies to achieve the strategic objectives proposed by senior management, by aligning business strategy with its basic organizational components: people, processes, technology and applications. In the present article an investigation is made about the AE, presenting its definition, the State of the Art, components, methodologies, tools of the AE, frames of reference, among others; The methodology used is based on the documentary analysis and review of the literature, as a study technique. Finally, a proposal to define the AE is established, considering what has been researched in the literature, and some relevant conclusions of the study are presented.